Role of mammalian target of rapamycin signaling in autophagy and the neurodegenerative process using a senescence accelerated mouse-prone 8 model - Wang, Yanyong (Exp Ther Med, 2017)
The mammalian target of rapamycin (mTOR) kinase is an inhibitor of autophagy, which is an intracellular system involved in the degradation of long-lived proteins and organelles in lysosomes. Recent evidence suggests that the steady incline in mTOR function during aging may be associated with the cognitive decline related to aging and may also promote development of Tau pathology. At present, the senescence accelerated mouse prone 8 (SAMP8) is an experimental model that has been proposed for the study of age-related neurodegenerative changes associated with aging. In the present study, mTOR signaling in the hippocampus of SAMP8 newborn mice and in the control-strain SAMR1 mice was investigated. Consequently, hyper phosphorylated Tau (pS199 or pS396) and upregulated mTOR activity were observed in SAMP8 when compared with SAMR1; however, 0.5 µM rapamycin administration significantly reduced the levels of phosphorylated Tau and p70S6K (pT389) in SAMP8 mice. Related to these findings, SAMP8 exhibited an increase in the neuronal loss of hippocampus that was associated with lower levels of anti-apoptotic proteins. These results indicate that mTOR signaling participates in the neurodegenerative process and rapamycin administration may protect neurons of SAMP8 mice and may have a potential role in curing cognitive decline.